Pengaruh Pelatihan Kerja Dan Disiplin Kerja Terhadap Produktivitas Kerja Pegawai Dengan Kompetensi Kerja Sebagai Variabel Intervening Pada Pegawai Kantor Bupati Kabupaten Pesisir Selatan - Fadila Nanda Putri; Yulasmi; Selvi Yona Sari (CV. ITTC INDONESIA, 2025)
This research aims to examine the influence of Job Training and Work Discipline on Employee Work Productivity with Work Competence as an Intervening Variable. In this research, Structrual Equation Modeling (SEM) analysis tools were used using Partial Least Square (PLS). The research results show that there is a positive and significant influence of Job Training on Job Competence. There is a positive and insignificant effect of Work Discipline on Work Competence. There is a positive and significant influence of Job Training on Work Productivity. There is a positive and insignificant effect of Work Discipline on Work Productivity. There is a positive and significant influence of Work Competence on Work Productivity. There is a positive and significant influence of Job Training on Work Productivity through Job Competency. There is a positive and insignificant influence of Work Discipline on Work Productivity through Work Competence.